Peran Bea dan Cukai Kualanamu Dalam Melaksanakan Penegakan Hukum Atas Tindak Pidana Penyelundupan Baby Lobster (Studi Putusan Nomor 1758/Pid.B/2020/PN. Lbp) - Bobby Hartanto Sinaga; Rizkan Zulyadi; M. Ridha Haikal (Mahesa Research Center, 2023)
The purpose of this study was to examine and analyze the legal arrangements regarding customs for smuggling of baby lobsters according to the provisions of laws and regulations in Indonesia, the roles and constraints carried out by Kualanamu Customs and Excise officers in carrying out law enforcement for the crime of baby lobster smuggling. The nature of this research is descriptive analysis, and the approach used in this research is an empirical approach. The results of the study stated that the legal regulation regarding customs for baby lobster smuggling according to the provisions of laws and regulations in Indonesia is the Regulation of the Minister of Maritime Affairs and Fisheries Number 17/PERMEN-KP/2021 concerning Management of Lobsters (Panurilus spp), Crabs (Scylla spp.), and Blue swimming crab (Portunus spp.) in the territory of the Republic of Indonesia. Kualanamu Customs and Excise officers act as customs law enforcers in collaboration with law enforcement officials. Kualanamu Customs and Excise officers play a role in inspecting goods, both incoming and outgoing goods. Kualanamu Customs and Excise officers play a role in making arrests of criminal offenders. The obstacles faced by Kualanamu Customs and Excise officers in carrying out law enforcement for the crime of baby lobster smuggling are Obstacles from Legal Regulations (Acts), Obstacles from Law Enforcement, Obstacles from Facilities and Infrastructure.